2023
DOI: 10.4274/tjo.galenos.2023.56249
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Outcomes of Intravitreal Anti-Vascular Endothelial Growth Factor Treatment for Diabetic Macular Edema in Türkiye: MARMASIA Study Group Report No. 1

Uğur Yayla,
Mehmet Orkun Sevik,
Veysel Levent Karabaş
et al.

Abstract: Objectives: This study aimed to report the demographic and clinical characteristics of diabetic macular edema (DME) patients treated with intravitreal injection (IVI) of anti-vascular endothelial growth factors (anti-VEGF) and provide an overview of outcomes during routine clinical practice in Türkiye. Materials and Methods: This retrospective, real-world study included 1,372 eyes (854 patients) treated with a pro re nata protocol by 21 ophthalmologists from 8 tertiary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Until recently, visual acuity and central macular thickness were set as reproducible and robust endpoints in virtually all prospective comparative anti-VEGF studies by the national health authorities [ 35 ]. However, the clinical study outcomes have regularly been found to be superior to real life, where case selection criteria of RCTs cannot be applied [ 36 , 37 , 38 , 39 ]. Moreover, visual gains and change in CRT are comparable between the marketed drugs and are thus not able to differentiate between the different drugs on the market [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, visual acuity and central macular thickness were set as reproducible and robust endpoints in virtually all prospective comparative anti-VEGF studies by the national health authorities [ 35 ]. However, the clinical study outcomes have regularly been found to be superior to real life, where case selection criteria of RCTs cannot be applied [ 36 , 37 , 38 , 39 ]. Moreover, visual gains and change in CRT are comparable between the marketed drugs and are thus not able to differentiate between the different drugs on the market [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, studies with longer follow-up periods may reveal subtle differences in efficacy of these anti-VEGF agents. Table 4 summarizes the outcomes of studies published over the last 12 years pertaining to anti-VEGF DME management [ 12 - 16 , 28 , 36 - 68 ] .…”
Section: Discussionmentioning
confidence: 99%